(Catechin and Epicatechin Analysis in Cacao Bean and Cacao products Using Liquid Chromatography Mass Spectrometry) - -, Subagja; -, Harmita; Suryadi, Herman; Junaidi, Lukman (Warta Industri Hasil Pertanian, 2009)
Cacao beans processing into product may affect active compound contents in the final products, especially catechin andÂ  epicatechin. Temperature treatments during cacao processing can induce epimerization reaction of (-)-epicatechin to be (-)-catechin. Therefore, catechin and epicatechin ratio in the samples would be change. The aim of the was to know imfluence during cacao beans processing, especially cathechin and epicatechin concentration. Samples taken during the process were cacao nib, cacao mass, cacao powder, and butter. Analysis of catechin and epicatechin in samples was carried out by liquid chromatography mass spectrometry. Analytical for catechin were using mobile phase A (0.1 %formic acid in deionized water) and mobile phase B (acetonitril-methanol = 50:50) at flow rate of 0.5 ml/min. gradient elution were set at 0 minutes (10%B), 15 minutes (35%B), 20 minutes (40%B), 30 minutes (50% B), 35 minutes (60% B), and 35.1 minutes (105 B). Mass sprectrometer was set at ESI voltage (-) 3500 volt, desolvation temperature 300 oC, nubelizer pressure 50 psi, desolvation gas 10L/min, and fragmentor voltage (-) 160 volt. Results of the research showed that of catechin and cacao nib, cacao mass and cacao powder were 1:21,7; 1:20,0; and respectively. Heat treatments during cacao mass processing sowed a decrease tendency of catechin and epicatechin concentrations.